Peculiarities of the development of subject-subject interaction in urban and rural schools of Kazakhstan: findings of sociological research of pedagogical problem - Puzikova, S. М. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2020)
Implementation of the subject-subject approach to a child as an equal partner; development of their subjectification in the learning process is now becoming the leading factor that ensures the process democratization and modernization of the educational process, which shapes the competitiveness of not only an individual but of the kazakhstan nation, as a whole. Subject-subject interaction means the establishment of the so-called “pedagogy of cooperation”, the co-management by participants in the educational process, and its democratization and humanization. An important peculiarity of the devel- opment of education in Kazakhstan is the threefold prevalence of rural schools over urban schools. As a percentage, this amounts to: 76.7% versus 23.3%. The most indicative in this regard is the situation in the South Kazakhstan region, which is the most densely populated. The implementation of the subject- based approach in school education in the region, the assessment of the degree of “modernization of public consciousness” and its ability to perceive the trends of humanization and democratization of the educational process are of scientific and practical interest in the context of fundamental reform in the educational system and Kazakhstan’s search for the educational ideal. The purpose of this article is to determine the specifics of the process of democratization in the relationships between of teachers and schoolchildren in urban and rural schools in the Republic of Ka- zakhstan to develop appropriate measures to improve the system and content of education. The methodology and method of the research includes analysis of foreign and domestic publications on the development of a democratic style of interaction in the teaching and educational process, with a view to cultural characteristics, regional differences in urban and rural environments; comparative-com- parative method, document analysis, survey methodologies were used, in accordance with the qualita- tive research strategy (questionnaires and in-depth interviews of schoolchildren and teachers). Research Findings. Currently, the educational environment of the Republic of Kazakhstan is rethink- ing the process of development of competences and the system of values of the younger generation, taking into account the increasing influence of the globalization process and the value transformation in Kazakhstan’s society. Proceeding from the fact that the opinions of schoolchildren and practicing teach- ers can suggest ways to improve the educational process while maintaining its educational potential, we have conducted a study in the target group of schoolchildren and teachers from urban and rural schools, comparing their approaches and suggestions on the development of a humanistic form of the relationship between participants in the educational process. The study demonstrated that there is difference in how students from urban and rural schools see the factors that shape the subject-subject relationships that develop during the educational process. These features should be considered during the transformation. The author of the article focused his attention on them in this publication. Key words: Subject-subject interactions, Modernization of education, Subjectivity of the shcoolchil- dren’s personality, cooperation in the educational process.